Interactive multimedia development for swimming learning and training. Issue 3 (March 2021) - Widiastuti, W; Sulaiman, I; Susilo, S; Hernawan, H; Mashud, M; Solahuddin, S; Pradityana, K
Abstract: The purpose of this research is to create interactive multimedia. This research and development uses Borg and Gall Research and Development (R&D) method which consists of 10 (ten) steps. The subject of this research was students of PJKR from three universities in three different areas in Indonesia. The subject of this research was students of PJKR from three universities in three different areas in Indonesia. The numbers of samples used to test the effectiveness of interactive multimedia are 45 people of experimental class and 45 people of control class. The research design used is the one group control pretest-posttest design experiment, the results of interactive multimedia development research show the value of Ztable> Zcount (89>-5, 7622), which means that there are significant differences between before and after the utilization of interactive multimedia. From these results it can be concluded that the development of interactive multimedia can be applied by the community to facilitate swimming training.